2013
DOI: 10.1371/journal.pone.0085170
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GRB2 and GAB1 Coexpression as an Unfavorable Prognostic Factor for Hepatocellular Carcinoma by a Combination of Expression Profile and Network Analysis

Abstract: AimTo screen novel markers for hepatocellular carcinoma (HCC) by a combination of expression profile, interaction network analysis and clinical validation.MethodsHCC significant molecules which are differentially expressed or had genetic variations in HCC tissues were obtained from five existing HCC related databases (OncoDB.HCC, HCC.net, dbHCCvar, EHCO and Liverome). Then, the protein-protein interaction (PPI) network of these molecules was constructed. Three topological features of the network ('Degree', 'Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 49 publications
(54 reference statements)
1
48
0
Order By: Relevance
“…This hypothesis is supported by the fact that EZH2 was shown to has a key role in the regulation of tumor angiogenesis and the decrease in its expression levels inhibited metastasis suggesting EZH2 as a potential therapeutic target to reverse the migration and invasion of cancer cells [40][41][42][43][44]. Like VCAN and EZH2 genes, several studies have shown that Grb2 has an important role in proliferation and angiogenesis of several tumors including HCC through its contribution in the signaling pathway of various angiogenic factors [17,22,45,46]. The overexpression of miR-564 was shown to inhibit the proliferation, migration and invasion of HCC cell lines through a direct effect on Grb2 gene [46].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis is supported by the fact that EZH2 was shown to has a key role in the regulation of tumor angiogenesis and the decrease in its expression levels inhibited metastasis suggesting EZH2 as a potential therapeutic target to reverse the migration and invasion of cancer cells [40][41][42][43][44]. Like VCAN and EZH2 genes, several studies have shown that Grb2 has an important role in proliferation and angiogenesis of several tumors including HCC through its contribution in the signaling pathway of various angiogenic factors [17,22,45,46]. The overexpression of miR-564 was shown to inhibit the proliferation, migration and invasion of HCC cell lines through a direct effect on Grb2 gene [46].…”
Section: Discussionmentioning
confidence: 97%
“…A cytoplasmic expression of VCAN protein was shown to be upregulated in HCC compared to matched normal tissues [19] and this overexpression was suggested as candidate biomarker for early stages of HCC [20]. In the same context, high expression of EZH2 [21] and Grb2 genes [22] were detected in HCC and also suggested as a promising diagnostic biomarkers of HCC.…”
Section: Introductionmentioning
confidence: 91%
“…Gene Ontology (GO) and Signaling Pathway Analysis GO analysis and signaling pathway analysis for the targets were analyzed through the Database for Annotation, Visualization, and Integrated Discovery (DAVID). 25) The results were assigned into 3 categories: biological processes, molecular function, and Kyoto encyclopedia of genes and genomes (KEGG) signaling pathway analysis. p ≀ 0.05 was regarded as significance.…”
Section: Networkmentioning
confidence: 99%
“…Centiscape [15], the app of Cytoscape, was used to calculate the degree measure of each node. Referring to the previous study of others [16,17], we determined the nodes whose degree were more than twice the mean degree value as hub genes. In order to explore more specific regulatory relationship in the above PPI network, the cluster analysis was performed by MCODE [18].…”
Section: The Construction and Analyzing Of Ppi Networkmentioning
confidence: 99%